Management Of Influencer Expression Regarding Vaccination Communication On Instagram - Kertamukti, Rama (Universitas Islam Negeri Raden Intan Lampung, 2022)
Middle January 2021, the death toll related to the Covid-19 pandemic reached 2 million people, and nearly 26 thousand people were recorded in Indonesia. The struggle of the Indonesian government to reduce the number of victims of COVID-19 by bringing the Sinovac vaccine and vaccinations to the community. Pros and cons occur in response to the covid-19 Vaccination with this Sinovac vaccine. The government's public communication strategy through influencers with many followers on Instagram is an option. The election of Instagram as Social media for vaccination communication is because Instagram is the most up-to-date social media, and it is easy to provide understanding because it involves information in the form of visuals and text to the public. In carrying out vaccination communications, these influencers create messages or information that are organic or organic. Amplified Word of Mouth so that vaccination communication can reach the community simultaneously. The subjects studied in this study were influencer accounts (@arielnoah and @dr. Tirta) which were selected by purposive sampling with qualitative research using the literature review method. The results showed that the influencers in each post on vaccination communication activities in the form of distributing content and information in the feed room, likes, and giving comments showed that vaccination communication activities carried out identity politics. Influencers on Instagram understand health and responsibility. The results of this study provide an overview of how influencers on their Instagram carry out impression management to convince the public that vaccines are safe and try to refer to the government's public campaign regarding covid-19 Vaccination.